Carbachol induces burst firing of dopamine cells in the ventral tegmental area by promoting calcium entry through L-type channels in the rat - Zhang, Lei (Blackwell Science Inc, 2005)
Enhanced activity of the central dopamine system has been implicated in many psychiatric disorders including schizophrenia and addiction. Besides terminal mechanisms that boost dopamine levels at the synapse, the cell body of dopamine cells enhances terminal dopamine concentration through encoding action potentials in bursts. This paper presents evidence that burst firing of dopamine cells in the ventral tegmental area was under cholinergic control using nystatin-perforated patch clamp recording from slice preparations. The non-selective cholinergic agonist carbachol excited the majority of recorded neurones, an action that was not affected by blocking glutamate and GABA ionotropic receptors. Twenty per cent of dopamine cells responded to carbachol with robust bursting, an effect mediated by both muscarinic and nicotinic cholinoceptors postsynaptically. Burst firing induced as such was completely dependent on calcium entry as it could be blocked by cadmium and more specifically the L-type blocker nifedipine. In the presence of the sodium channel blocker tetrodotoxin, carbachol induced membrane potential oscillation that had similar kinetics and frequency as burst firing cycles and could also be blocked by cadmium and nifedipine. Direct activation of the L-type channel with Bay K8644 induced strong bursting which could be blocked by nifedipine but not by depleting internal calcium stores. These results indicate that carbachol increases calcium entry into the postsynaptic cell through L-type channels to generate calcium-dependent membrane potential oscillation and burst firing. This could establish the L-type channel as a target for modulating the function of the central dopamine system in disease conditions.